Unexpected Attachments: A Literary Approach to the Term [ILLEGIBLE] in the Hebrew Bible - Britt, Brian M. 1964- (2003)
The biblical term [ILLEGIBLE], variously translated ‘loving kindness’ and ‘steadfast love’, displays a wide range of biblical uses and meanings. This article concentrates on poetic and narrative texts in which [ILLEGIBLE] appears surprisingly, often to denote unexpected attachments. While [ILLEGIBLE] is a formulaic term in covenant tradition, some poetic texts, notably Ps. 89, Isa. 54, and Lam. 3, place the term in striking contrast to its immediate context. Narrative cases of unexpected [ILLEGIBLE] include the attachments between Ruth and Naomi, David and Jonathan, Abraham and Sarah (in the wife-sister scenes), Yahweh and Israel, and three episodes about spies. By attending to the literary uses of [ILLEGIBLE], this article illuminates the place of [ILLEGIBLE] in biblical theology.